Bible and bedlam madness, sanism, and New Testament interpretation - Lawrence, Louise Joy 1975- (New York Bloomsbury Academic, 2018)
Bible and bedlam -- Ivory towers and the banishment of bedlam: reason, right minds, and sane privilege in biblical studies -- The curious incident of a Jew in the night-time: autistry and an encounter with Nicodemus -- Ex-centric women: intersecting marginalities and the madness narratives of Bessie Head, a Canaanite woman and Pythian slave girl -- Gatekeeping the madness of Jesus and Paul: negotiating mythologies of madness in an age of Neoliberalism -- Beyond bedlam? Keeping open[ing] minds in biblical interpretation
Includes bibliographical references and index
Reproduktion
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Bible -- Criticism, interpretation, etc; People with mental disabilities -- Religious life; People with disabilities in the Bible